Lecturers’ Challenges and Strategies in Teaching Maritime English Online to Students with Low English Proficiency - Latifa Ika Sari; Ria Hermina Sari (IAIN Salatiga, 2022)
This study aimed to investigate the problems faced by ESP lecturers when teaching low English proficiency students during online Maritime English lessons and their strategies in dealing with the problems. A questionnaire with six open-ended questions was distributed to 9 Maritime English lecturers from 6 different Maritime Polytechnics in Indonesia. A follow-up interview was conducted with four lecturers to obtain more detailed information regarding their online teaching practices, especially the difficulties and the strategies to mitigate them. The findings of this study revealed 3 (three) main problems faced by the lecturers. Firstly, students were reluctant to interact and participate in class activities. Secondly, students showed low motivation and interest in learning English. Thirdly, the lecturers needed extra time to explain the teaching materials. To overcome the problems, the lecturers used various texts, pictures, videos, or online platforms to expose students to maritime vocabulary. They also grouped the lower proficiency students with the higher proficiency students in a collaborative activity, designed class activities based on students’ learning styles, and employed various scaffolding techniques. Keywords: English for Specific Purposes (ESP) teaching, low English proficiency, Maritime English, online learning.